(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
This dialogic exchange discusses the development and outcomes of an interactive installation that uses live-animated digital effects to projection-map viral “shadowpox” onto the player’s body. The project was developed by Alison Humphrey, then a Vanier Scholar and York University PhD candidate in cinema and media studies, in collaboration with Caitlin Fisher, director of York University’s Immersive Storytelling Lab, and Steven J. Hoffman, director of the Global Strategy Lab and scientific director of the Canadian Institutes of Health Research’s Institute of Population and Public Health, with support from technical director and creative coder LaLaine Ulit-Destajo, epidemiologist Susan Rogers Van Katwyk, and website programmer Sean Sollé, as part of the three-year interdisciplinary project <Immune Nations>, and culminated with an exhibition at UNAIDS during the 70th World Health Assembly in Geneva, Switzerland.